The resonance between the electromagnetic field and electrons in the helicon plasma source of a magnetoplasma rocket engine - Yang, Zhenyu; Fan, Wei; Han, Xianwei; Tan, Chang (Frontiers in Physics, 2023)
The helicon plasma source is of great significance for the Magnetoplasma Rocket Engine (MPRE) to be an effective propulsion device. In this paper, a multi-fluid, two-dimensional, axisymmetric model coupled with the electromagnetic field was developed to simulate the helicon plasma source in MPRE. The simulation results demonstrate that, the operation mode of the helicon plasma source in MPRE gradually converts to high-order wave mode and there appears the resonance between the electromagnetic field and electrons; due to the resonance, the deposit power density inside the plasma increases significantly and the plasma density is two orders of magnitude higher than that in Inductively Coupled Plasma (ICP) source; as the magnetic field intensity increases, the helicon plasma source enters into high-order wave mode which suggests that MPRE can improve the utilization rate of the working medium by a stronger magnetic field.